Kesiapan ibu dalam melahirkan sehat di wilayah kerja Puskesmas Brebes Jawa Tengah - Irene Jesihka Pandiangan; Ede Surya Darmawan (Berita Kedokteran Masyarakat (BKM), 2018)
Mother's readiness in healthy childbirth in Brebes Health Center of Central JavaPurpose: Although health workers have made classes of pregnant women to have a healthy childbirth, very few evaluations of these programs existed for Indonesian context. This study examines health workers and socioeconomic factors effects on mother's readiness to deliver healthy children. Methods: A survey of 100 pregnant women in the working area of the Brebes Health Center in Brebes Regency, Central Java Province, in 2018. Data collection using questionnaires and pregnancy records in the MCH Handbook. Results: A quarter of pregnant women in this study were not ready for a "healthy childbirth process" (24%). Mothers with higher education have three and a half times more than those with low education. Mothers who received health support in the ANC were three times more prepared than those who did not need ANC support. Conclusions: Most pregnant women have adequate readiness to deliver a healthy child. Mothers with low education were less likely to be ready to have a healthy childbirth. Health worker support to mothers during antenatal care is critical for a healthy childbirth. Puskesmas workers should reach mothers who have no ANC visit and educate them, in particular, those from low-education mothers.